Instituto Federal de Educação, Ciência e Tecnologia : análise de processos sociais de egressos do ensino superior - Wingler, Silvani da Silva (2018)
The main objective of this study is to analyze the paths taken by students who have graduated from higher education, class in mode and at a distance, in the figuration of the Federal Institute of Education, Science and Technology of Espírito Santo - Ifes, Campus Cachoeiro de Itapemirim. Survey of referential information, location and public needs egress from this figuration; data on the occupational and social spaces occupied by the former students were systematized; it was understood, through the discourse of the graduates, their course in higher education; the students' perception of the completed curriculum was analyzed, based on Norbert Elias's theory of figurative sociology, based on the concepts of "figuration", "interdependence" and "social processes". Methodologically, we used the case study as a guideline of the course of the study and the use of document study, online questionnaire with closed and open questions, semi-structured interviews and focus group as procedures for data collection. The indicators based on the responses of the graduates allowed the verification of the objectives established in the study, such as that the graduates are very satisfied with the received education, that their majority occupies space of work in the area of formation in the public networks (like effective server or contracted) and in the private network, being mostly composed of workers or participants of some program coming from student assistance during the course. The analysis, interpretation and conclusion, provided by a diversified collection of data including direct listening of the graduates, represent important sources of data to the institution in order to evaluate the offered education, to know if the graduates are working in their area of formation or are unemployed, if they are satisfied with the contents acquired for the exercise of their profession and, above all, if the Federal Institute of Education, Science and Technology of Espírito Santo fulfills its mission of offering education and production of socially valid knowledge for the world of work, for the verticalization of studies and for the exercise of citizenship.